2020
DOI: 10.1111/pirs.12479
|View full text |Cite
|
Sign up to set email alerts
|

Regional diffusion of military regimes in sub‐Saharan Africa

Abstract: Military dictatorships have been decreasing in number and concentrating in Africa. This paper analyses their spatial diffusion in sub-Saharan Africa between 1978 and 2014 applying a Bayesian SAR Probit regression. We find a significant and positive spatial coefficient only in the aftermath of the Cold War. This result suggests that once the global order of the Cold War vanished, geography took back its role and regional factors became crucial in shaping the institutional landscape. The evidence is interpreted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 68 publications
0
1
0
Order By: Relevance
“…[ 36 , 42 ]. Other studies found that the military's decreasing influence in politics and state matters positively impacts social development and promotes resource allocation, leading to socioeconomic development [ 39 , 41 ]. However, few studies in Bangladesh, Malaysia, Pakistan, and Turkey have discussed the positive effects of relatively moderate military inclusion, such as tourism industry reforms and improved civilian-military relations, on public policy and state social development [ 15 , 37 , 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…[ 36 , 42 ]. Other studies found that the military's decreasing influence in politics and state matters positively impacts social development and promotes resource allocation, leading to socioeconomic development [ 39 , 41 ]. However, few studies in Bangladesh, Malaysia, Pakistan, and Turkey have discussed the positive effects of relatively moderate military inclusion, such as tourism industry reforms and improved civilian-military relations, on public policy and state social development [ 15 , 37 , 40 ].…”
Section: Resultsmentioning
confidence: 99%